Development and Validation of Multiplex Quantitative Real-Time PCR Assays for Simultaneous Detection and Differentiation of HTLV-1 and HTLV-2, Using Different PCR Platforms and Reagent Brands - Gonçalves, Maria Gisele; Fukasawa, Lucila Okuyama; Campos, Karoline Rodrigues; Higa, Fábio Takenori; Caterino-de-Araujo, Adele (Frontiers in Microbiology, 2022)
Brazil currently has the highest number of individuals infected with human T-lymphotropic virus 1- and 2- (HTLV-1 and HTLV-2) globally. At present, neither molecular protocols nor commercial assays are available for HTLV-1/-2 diagnosis or validated by the Brazilian Ministry of Health regulatory agency (ANVISA). We developed and validated two in-house multiplex quantitative real-time PCR for HTLV-1/-2 (mqPCR_HTLV) assays, targeting the pol and tax genes, for the simultaneous identification of HTLV-1, HTLV-2, and the albumin reference gene. The robustness of the assays was evaluated on two platforms using seven commercial master mix formulations. The reactions employed double plasmids (pHTLV1-Alb and pHTLV2-Alb) for the standard curve’s construction and for expressing the detection limit of the assays. They were able to detect 10 and 10 copies of HTLV-1 and 10 and 70 copies of HTLV-2 for the tax and pol targets, respectively. High efficiency was obtained using both the platforms and all the reagents evaluated and were successfully reproduced by other analysts. DNA samples from HTLV-1/-2-infected and non-infected patients and from HIV/HTLV-coinfected patients were evaluated to determine the feasibility of their use in routine diagnosis. The mqPCR_HTLV (pol and tax) assays demonstrated an overall specificity of 100% and a sensitivity of 97.4% when testing samples from patients without HIV infection, and sensitivities of 77.1% (pol) and 74.6% (tax) in samples from HIV/HTLV-coinfected patients. In addition, they resolved the issue of HTLV western blotting (WB) indeterminate and WB-untyped results in 45.5% and 66.7% of cases, respectively. The developed mqPCR_HTLV (pol and tax) assays indicated their feasibility for efficient and reliable HTLV diagnosis in various core facility laboratories under different conditions and supplies.